Buckwheat: An Underutilized Himalayan Crop with Multifaceted Nutraceutical Benefits - Raina, Kirti; Kumari, Ruchika; Thakur, Palak; Sharma, Rohit; Chaudhary, Ashun (Recent Advances in Food Nutrition & Agriculture, 2025)
The human population is growing and alternate food options are needed to provide food and nutritional security to mankind. Reduced agricultural output as a result of climate change and increased demand for grains because of continuous population growth have created a gap between demand and supply of food. Buckwheat is a pseudocereal crop plant with high nutritional value that can be included as an alternate food in our diet. It is a traditional crop plant grown in the high mountains of the Himalayas for food as well as fodder. It completes its life cycle in 3-4 months, so is mostly grown as a second crop in between main crops like maize and barley. It also acts as a green manure by improving the phosphorus content of the soil. Buckwheat has high nutritional value as it is rich in essential amino acids, vitamin B, trace elements, and other nutrients. The main bioactive compounds identified in buckwheat are rutin, quercetin, isoquercetin, d-chiroinositol, resveratol, and vitexin, which are responsible for its pharmacological properties. Research focused on value addition by exploring its nutritional, pharmaceutical, and other alternative uses of commercial importance, is needed for reviving buckwheat cultivation practices and its conservation. Considering the multifarious applications of buckwheat, this review summarizes the currently available knowledge on the agronomic and nutraceutical significance of buckwheat to project its value as a future crop in the avenue of agriculture and functional food.
Keywords: essential amino acids